2020
DOI: 10.1021/acschembio.0c00477
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Phycocyanobilin Synthesis for Genetically Encoded Phytochrome-Based Optogenetics

Abstract: Optogenetics is a powerful technique using photoresponsive proteins, and light-inducible dimerization (LID) systems, an optogenetic tool, allow to manipulate intracellular signaling pathways. One of the red/far-red responsive LID system, phytochrome B (PhyB)-phytochrome interacting factor (PIF), has a unique property of controlling both association and dissociation by light on the second time scale, but PhyB requires a linear tetrapyrrole chromophore such as phytochromobilin or phycocyanobilin (PCB), and such … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…However, some dimerizers require the addition of cofactors that are not synthesized by mammalian cells, such as the cofactors required for phytochromes. In this case, cell media should be supplemented with phycocyanobilin (PCB) to ensure the functionality of the photosensitive protein (Toettcher, Gong, Lim, & Weiner, 2011a), or the user should use cell lines engineered for the synthesis of PCB (Uda et al., 2020).…”
Section: Commentarymentioning
confidence: 99%
“…However, some dimerizers require the addition of cofactors that are not synthesized by mammalian cells, such as the cofactors required for phytochromes. In this case, cell media should be supplemented with phycocyanobilin (PCB) to ensure the functionality of the photosensitive protein (Toettcher, Gong, Lim, & Weiner, 2011a), or the user should use cell lines engineered for the synthesis of PCB (Uda et al., 2020).…”
Section: Commentarymentioning
confidence: 99%
“…The cDNAs of PcyA, HO1, Fd , and Fnr were originally derived from Thermosynechococcus elongatus BP-1 as previously described (Uda et al, 2020). The mitochondrial targeting sequence (MTS; MSVLTPLLLRGLTGSARRLP) was derived from human cytochrome C oxidase subunit VIII.…”
Section: Methodsmentioning
confidence: 99%
“…Another potential issue is that the supplemented PCB may not reach proper concentrations in certain tissues in vivo, which may affect the potency of PhotoGal4. However, it has been shown that mammalian cultured cells expressing cyanobacterial enzymes PcyA and HO1 can successfully transform endogenous heme groups into PCB (Kyriakakis et al, 2018;Muller et al, 2013b;Uda et al, 2017;Youichi Uda et al, 2020). We strongly believe that genetic synthesis of PCB will pave the way for more practical applications of PhotoGal4.…”
Section: Limitations Of the Studymentioning
confidence: 96%